Plan de comunicación interna para el centro local Ecu-911 Esmeraldas - Reyes Demera, Patricia Stefanía (2015)
This titling project is a proposal of a Plan of internal communication to the local center ECU-911 in Esmeraldas. It encompasses three chapters. The first one offers a theoretical framework based on the lines of structuralism and functionalism, in its content we establish the main concepts of organizational communication and its importance. In the second chapter we present the organization of the Local Centre ECU -911 Esmeraldas to the reader while we develop a diagnostic to know the communicational situation. To prepare the diagnosis we use tools such us the interview and survey. The third chapter we analyzed the communication status of the center and designed each key strategy according to the diagnosis results.